Подолання російського імперського дискурсу в інтелектуальному просторі Європи як умова реалізації цивілізаційного вибору України - Мусієнко, Ірина Володимирівна (Київський національний університет ім. Т. Г. Шевченка, 2015)
У статті аналізується вплив російського імперського дискурсу на європейське сприйняття і прийняття стратегічних політичних рішень щодо України.

Civilizational choice of Ukraine in favor of Euro-Atlantic integration is outlined in its political conceptual legal documents - "National Security Strategy of Ukraine", the Laws "On Foundations of Domestic and Foreign Policy of Ukraine". They determine the integration into the political and economic structures of the European Union as a priority direction of foreign and domestic policy of Ukraine which shares common with the EU values and strategic goals. Prerequisites of Ukraine’s civilizational choice implementation is a new positioning of the state and its rebranding, creating of an integrated communication policy, strong international lobby, its positive image as a European country, overcoming the stereotype of "Alien, Different" in perceptions of Ukraine by foreign target audiences, European supranational identity designing, strengthening its presence in European social and cultural space. However, the political elite of Ukraine failed to develop a national strategy on protection of national interests in the international arena. Experts point out serious shortcomings and mistakes in creating a coherent communication policy, implementation of effective foreign management of the state, qualified state imaging, strengthening Ukraine's presence in socio-cultural space of Europe, state support for fundamental Ukrainistics and Ukrainian Studies. Thus, there is an urgent need to develop science-based strategy of Ukrainian national discourse protecting, foreign state image promoting, which will guarantee the implementation of civilizational choice of Ukraine – Euro-Atlantic integration.
Overcoming of Russian Imperial Discourse in Intellectual Space of Europe as a Precondition of Implementation of Ukrainian Civilization Choice
Keywords: Imperial Discourse; Civilizational Choice; Postcolonialism; Euro-Atlantic Integration; Ukraine; Russia; цивілізаційний вибір; Європа; євроатлантична інтеграція; імперський дискурс; Україна